Project Scheduling Analysis Using the Precedence Diagram Method (PDM) Case Study: Surabaya’s City Outer East Ring Road Construction Project (Segment 1) - Romadhona, Syahrur; Kurniawan, Fredy; Tistogondo, Julistyana (Malikussaleh University, Aceh, Indonesia, 2021)
The project acceleration by the Crash Program is one of the ways that is often used to make time and cost efficiency on an ongoing project. Acceleration of project completion time will affect the efficiency of equipment and labor productivity. In the case study of the Surabaya Outer East Ring Road Project Construction Segment 1, a project that has the potential to be accelerated is discussed in order to obtain efficiency values in terms of time and cost, Project acceleration by means of the Crash Program using the Precedence Diagram Method (PDM) method to determine the value of efficiency. This project uses resources, in this research the software used is Microsoft Project 2016. The research method used is to design network planning, find the critical path for each job, determine the work that has the potential to be accelerated, calculate the crash cost in additional working hours. and work shifts, calculating direct costs and indirect costs for each activity that changes due to changes in the duration of implementation, calculating the cost slope. Application of the Crash Program in the work of Asphalt Concrete Surface Layers (AC) thick 5 cm in the project will have an impact on increasing the time efficiency previously planned from 180 working days to 175 working days and efficiency with the difference in project costs of Rp. 18.313.935,8 with a ratio of 0,997 between the PDM method compared to the cost of the contract value calculated using the crashing project method.